A novel rapid access testicular cancer clinic: prospective evaluation after one year. (February 2016) - Carey, K.; Davis, N.; Elamin, S.; Ahern, P.; Brady, C.; Sweeney, P.
Abstract Background Our institution has recently developed a rapid access outpatient clinic to investigate men with testicular lumps and/or pain suspicious for testicular cancer (TCa). Aims To present our experience after 12 months. Methods All referrals to the rapid access testicular clinic (RATC) clinic were prospectively analysed from 01/01/2013 to 01/01/2014. The primary outcome variable was incidence of TCa in the referred patient cohort. Secondary outcome variables were waiting times prior to clinical review and waiting times prior to radical orchidectomy in patients diagnosed with TCa. Results Seventy-four new patients were referred to the RATC during the 1-year period and the mean age was 34 (range 15–81 years). TCa was the most common diagnosis and was found in 18 (25 %) patients. Patients diagnosed with TCa underwent radical orchidectomy, a median of 3 (range 1–5) days after their initial GP referral. Patients requiring surgical intervention for benign scrotal pathology underwent their procedure a median of 32 (range 3–61) days after their initial referral. Of the 18 patients diagnosed with TCa, 9 (50 %) were diagnosed with a seminomatous germ cell tumour on histopathology. Conclusion The RATC is a new initiative in Ireland that provides expedient and definitive treatment of patients with newly diagnosed TCa. Early treatment will ultimately improve long-term prognosis in this patient cohort.